18-Fluorodeoxyglucose Positron Emission Tomography-Computed Tomography to Guide Aortic Arch Replacement in Relapsing Polychondritis - Pfister, Raymond; Messe, Maria; Niclauss, Lars; Kirsch, Matthias; Haller, Claude; Delay, Dominique (AORTA, 2019)
Relapsing polychondritis (RP) is a rare progressive autoimmune disease. The cardiovascular system is rarely involved. The authors report the case of a young woman with RP aortic arch aneurysm and symptomatic cerebral vessels stenosis. A positron emission tomography-computed tomography (PET–CT) indicated areas with activity and guided the surgery. Aortic arch with proximal vessels was successfully replaced. The PET–CT may be useful to assess the risks and determine healthy zones for potential anastomotic sites.
Keywords: relapsing polychondritis; vasculitis; PET–CT; aorta; aortic arch replacement